Loss of Cervical Sympathetic Chain Input to the Superior Cervical Ganglia Affects the Ventilatory Responses to Hypoxic Challenge in Freely-Moving C57BL6 Mice - Getsy, Paulina M.; Coffee, Gregory A.; Hsieh, Yee-Hsee; Lewis, Stephen J. (Frontiers in Physiology, 2021)
The cervical sympathetic chain (CSC) innervates post-ganglionic sympathetic neurons within the ipsilateral superior cervical ganglion (SCG) of all mammalian species studied to date. The post-ganglionic neurons within the SCG project to a wide variety of structures, including the brain (parenchyma, cerebral arteries), upper airway (e.g., nasopharynx, tongue) and submandibular glands. The SCG also sends post-ganglionic fibers to the carotid body (e.g., chemosensitive glomus cells, and microcirculation), however the function of these connections are not established in the mouse. In addition, nothing is known about the functional importance of the CSC-SCG complex (including input to the carotid body) in the mouse. The objective of this study was to determine the effects of bilateral transection of the CSC on the ventilatory responses (e.g., increases in frequency of breathing, tidal volume and minute ventilation) that occur during and following exposure to a hypoxic gas challenge (10% O2, 90% N2) in freely-moving sham-operated (SHAM) adult male C57BL6 mice, and in mice in which both CSC were transected (CSCX). Resting ventilatory parameters (19 directly recorded or calculated variables) were similar in the SHAM and CSCX mice. There were numerous important differences in the responses of CSCX and SHAM mice to the hypoxic challenge. For example, the increases in frequency of breathing (and associated decreases in inspiratory and expiratory times, end expiratory pause, and relaxation time), and the increases in minute ventilation, expiratory drive, and expiratory flow at 50% exhaled tidal volume (EF50) occurred more quickly in the CSCX mice than in the SHAM mice, although the overall responses were similar in both groups. Moreover, the initial and total increases in peak inspiratory flow were higher in the CSCX mice. The overall increases in tidal volume during the latter half of the hypoxic challenge were greater in the CSCX mice. The ventilatory responses that occurred upon return to room-air were essentially similar in the SHAM and CSCX mice. Overall, this novel data suggest that the CSC may normally provide inhibitory input to peripheral (e.g., carotid bodies) and central (e.g., brainstem) structures that are involved in the ventilatory responses to hypoxic gas challenge in C57BL6 mice.